IMPLEMENTASI BARCODE PADA APLIKASI SISTEM INFORMASI MANAJEMEN GUDANG BERBASIS DESKTOP - Zega, Theoputra Berkat; Suprihadi, Suprihadi (UNIVERSITAS STEKOM, 2025)
The rapid development of information technology has significantly influenced warehouse management, particularly in enhancing operational effectiveness and efficiency. Equal Billiard as provider of billiard equipment and facilities, faces challenges in inventory management due to manual recording processes, such as data errors, data loss and delay in item tracking. This study aims to design, implement and evaluate a desktop-based warehouse management information system integrated with barcode technology. The research employs The Research and Development (R&D) method, consisting of needs analysis, system design, development, implementation and evaluation stages. The system was developed using Python programming language and SQLite database. The results indicate that the implementation of barcodes improves recording accuracy, accelerates data entry and facilitates the identification of incoming and outgoing items. Field evaluation shows that the system helps staff minimize human error and produce faster, more accurate inventory reports. In conclusion, the barcode-based warehouse management information system successfully enhances the effectiveness of inventory management at Equal Billiard. Future improvements may include integration with web or mobile-based platforms and the adoption of cloud database to support data flexibility and security.